Joints for furniture making / Ainorshah Ismawani Ismail - Ismail, Ainorshah Ismawani (2007)
Joining wood is an important activity in furniture industries. There are many types of joints used to making furniture like mortise and tenon joint, finger joints, butt joints and others. Besides the several joints, fasteners are also used for strength during wood working.